Organizational distance and use of collateral for business loans - Jiménez, Gabriel; Salas, Vicente; Saurina, Jesús (Journal of Banking & Finance, 2009)
This paper examines the effect of organizational distance (i.e. distance between the headquarters of the bank that grants a loan and the location of the borrower) on the use of collateral for business loans by Spanish banks on the basis of the recent lender-based theory of collateral [Inderst, R., Mueller, H.M., 2007. A lender-based theory of collateral. Journal of Financial Economics 84, 826–859.]. We find that, for the average borrower, the use of collateral is higher for loans granted by local lenders than by distant ones. We also show that the difference in the likelihood of collateral in loans granted by local lenders, relative to distant lenders, is higher among older and larger firms, than, respectively, younger and smaller firms. We also find that banks use lending technologies that are different for near and for distant firms, in response to organizational diseconomies.